Spontaneous Thought and Vulnerability to Mood Disorders: The Dark Side of the Wandering Mind. (September 2016) - Marchetti, Igor; Koster, Ernst H. W.; Klinger, Eric; Alloy, Lauren B.
There is increasing interest in spontaneous thought, namely task-unrelated or rest-related mental activity. Spontaneous thought is an umbrella term for processes like mind-wandering, involuntary autobiographical memory, and daydreaming, with evidence elucidating adaptive and maladaptive consequences. In this theoretical framework, we propose that, apart from its positive functions, spontaneous thought is a precursor for cognitive vulnerability in individuals who are at risk for mood disorders. It is important that spontaneous thought mostly focuses on unattained goals and evaluates the discrepancy between current and desired status. In individuals who stably (i.e., trait negative affectivity) or transitorily (i.e., stress) experience negative emotions in reaction to goal-discrepancy, spontaneous thought fosters major cognitive vulnerabilities (e.g., rumination, hopelessness, low self-esteem, and cognitive reactivity), which, in turn, enhance depression. Furthermore, we also highlight preliminary links between spontaneous thought and bipolar disorder. The evidence for this framework is reviewed, and we discuss theoretical and clinical implications of our proposal.